Green synthesis Quantum Dots (GQD) from Coconut Husk (Cocos nucifera L) the Evaluation for Antibacterial and Cytological Activity - Alsadooni, Jaafar Faez Kadhim; Obada, Sura Razzaq Khudhair (International Journal of Advanced Science and Technology, 2019)
In this paper, synthesis of Graphene quantum dots (GQDs) from coconut husk which is a normal biomass as a biosynthesis precursor utilizing a single step hydrothermal carbonization. Structural and morphological characterization of these GQDs was carried out using XRD, Raman, and FTIR. As synthesized at the same time XRD results established their crystalline nature. Raman spectroscopic measurements exhibited the characteristic "D" (a thousand cm−1) and "G" (3500 cm−1) bands confirming the formation of low dimensional graphene nanostructures. Optical properties of these GQDs had been probed making use of UV-seen spectrometry and room temperature Photoluminescence measurements. The UV-vis spectrum confirmed a powerful absorption at 320 nm. These GQDs exhibited fluorescence regularly at 440 nm when excited at one of kind wavelengths. The fluorescence of GQDs was observed to be sensitive to pH linearly over the pH range of four–12 which may also be exploited for pH sensor purposes. FTIR spectroscopy has proven the presence of hydroxyl and carboxyl practical moieties on the surface of the GQDs, which play a significant position in surface passivation leading to extra steady nanoparticle dispersions. Coconut Husk extract-Graphene quantum dots confirmed greatest antimicrobial undertaking towards several bacteria species akin to Pseudomonas aeruginosa, Streptococcus mutans, Streptococcus aureus and E coli. Established on the findings, Coconut Husk might be exploited in developing bioactive pharmaceutical medicines for mighty therapy of cancer.